Increased Voluntary Alcohol Consumption in Mice Lacking GABAB(1) Is Associated With Functional Changes in Hippocampal GABAA Receptors - Floris, Gabriele; Asuni, Gino Paolo; Talani, Giuseppe; Biggio, Francesca; Pisu, Maria Giuseppina; Zanda, Mary Tresa; Contu, Liliana; Maciocco, Elisabetta; Serra, Mariangela; Follesa, Paolo (Frontiers in Behavioral Neuroscience, 2022)
Gamma-aminobutyric acid type B receptor (GABABR) has been extensively involved in alcohol use disorders, yet the mechanisms whereby this receptor modulates alcohol drinking behavior remains murky. In this study, we investigate alcohol consumption and preference in mice lacking functional GABABR by using the 2-bottle choice paradigm. We found that GABAB(1) KO, and Hz mice drank higher amounts of alcoholic solution, preferred alcohol over water and reached higher blood alcohol concentrations (BAC) compared to WT littermates. The GABABR agonist GHB significantly reduced alcohol consumption in GABAB(1) Hz and WT but not in KO mice. Next, due to a functional crosstalk between GABABR and δ-containing GABAA receptor (δ-GABAAR), we profiled δ subunit mRNA expression levels in the brain regions in which this crosstalk has been characterized. We found loss of alcohol sensitive GABAAR δ subunit in the hippocampus of alcohol naive GABAB(1) KO mice that was associated with increased ɣ2 subunit abundance. Electrophysiological recordings revealed that these molecular changes were associated with increased phasic inhibition suggesting a potential gain of synaptic GABAAR responsiveness to alcohol that has been previously described in animal model of excessive alcohol drinking. Interestingly, voluntary alcohol consumption did not revert the dramatic loss of hippocampal δ-GABAAR occurring in GABAB(1) KO mice but rather exacerbates this condition. Finally, we profiled hippocampal neuroactive steroids levels following acute alcohol administration in GABAB(1) KO and WT mice due to a previous involvement of GABABR in the regulation of cerebral levels of these compounds. We found that systemic administration of alcohol (1.5 g/kg) did not produce alcohol-induced neurosteroids response in GABAB(1) KO mice but elicited an expected increase in hippocampal level of progesterone and 3α,5α-THP in WT controls. In conclusion, we show that genetic ablation of GABAB(1) subunit results in increased alcohol consumption and preference that were associated with functional changes of hippocampal GABAAR, suggesting a potential mechanism by which preference for alcohol consumption is maintained in GABAB(1) KO mice. In addition, we documented that GABAB(1) deficiency results in lack of alcohol-induced neurosteroids and we discuss the potential implications of this finding in the context of alcohol drinking and dependence.